2002
DOI: 10.1001/archsurg.137.9.1044
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Pancreaticojejunostomy Techniques According to Pancreatic Texture and Duct Size

Abstract: Selection of proper pancreaticojejunostomy techniques according to pancreatic texture and the main duct size reduces the pancreatic fistula rate.Design and Patients: Data from 50 consecutive patients undergoing pancreatoduodenectomy with 3 different anastomotic techniques prospectively used according to pancreatic texture and the main duct size were analyzed. Duct-invagination anastomosis was selected for pancreata with a small duct (n=34 [29 with a soft texture and 5 with a hard texture]). Stitches between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
1
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 9 publications
4
80
1
11
Order By: Relevance
“…Patients in whom the pancreatic texture has a hard consistency have been reported to be at lower risk for pancreatic leakage than those patients who have a pancreatic parenchyma with a soft or intermediate consistency [22,23] . The texture of the pancreatic parenchyma has been reported to be correlated with the pancreatic duct diameter [24] , in considering the ease in performing a pancreatic duct-to-jejunum mucosa anastomosis, such a simple comparison requires more consideration. The pancreatic duct diameter has been correlated with pancreatic leakage [5] , and our study showed that 136 (79.1%) patients had evidence of pancreatic duct dilatation by histopathologic reports, confirming the correlation between pancreatic duct size and pancreatic fistula development (P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Patients in whom the pancreatic texture has a hard consistency have been reported to be at lower risk for pancreatic leakage than those patients who have a pancreatic parenchyma with a soft or intermediate consistency [22,23] . The texture of the pancreatic parenchyma has been reported to be correlated with the pancreatic duct diameter [24] , in considering the ease in performing a pancreatic duct-to-jejunum mucosa anastomosis, such a simple comparison requires more consideration. The pancreatic duct diameter has been correlated with pancreatic leakage [5] , and our study showed that 136 (79.1%) patients had evidence of pancreatic duct dilatation by histopathologic reports, confirming the correlation between pancreatic duct size and pancreatic fistula development (P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The rates of fistula are significantly lower in patients undergoing duct to mucosa anastomosis when compared to invagination [44,[52][53][54][55]. Bassi et al in a prospective study showed no difference in the technique used [56].…”
Section: Duct To Mucosa Versus Invaginationmentioning
confidence: 98%
“…Amongst all, texture of the gland remains the most important predictive factor. The soft and fatty texture of the pancreas [38][39][40][41][42][43][44][45][46] with a non dilated duct (duct size < 3 mm) [45,46] has a higher incidence of fistula when compared to fibrotic/atrophic pancreas with a dilated duct. Increased secretion of pancreatic juice is seen in patients with soft or normal pancreatic remnant and is associated with increased rates of POPF [41].…”
Section: Organ and Disease Related Factorsmentioning
confidence: 99%
“…Pancreatic stump tissue condition and pancreatic duct diameter are considered to be the most significant risk factors of PDA dehiscence [16][17][18]. To reduce PDA dehiscence rate, the authors [6, [19][20][21] suggest an individual approach to anastomosis, which is determined, primarily, by the pancreatic condition and pancreatic duct diameter. Currently, there is no lifetime morphometric assessment of pancreatic parenchyma.…”
Section: Methodsmentioning
confidence: 99%
“…In literature one can find just a few reports on the criteria to estimate the pancreatic condition. So, Suzuki et al [21] have determined the pancreatic parenchyma condition (dense or soft) based on the difficulty or easiness in pancreatic tissue dissection by an ultrasound scalpel. We have suggested a criterion of "ligature incision of tissue".…”
Section: Methodsmentioning
confidence: 99%